2022
DOI: 10.1177/09639470221106021
|View full text |Cite
|
Sign up to set email alerts
|

Linking Emotions to Surroundings: A Stylistic Model of Pathetic Fallacy

Abstract: This article aims to provide a stylistically founded model of pathetic fallacy (PF hereafter). Pathetic fallacy is a Romantic literary technique used in art and literature to convey emotions through natural elements. This technique has been researched mostly from a literary viewpoint, but no linguistic model exists to define it. It is difficult to identify it precisely or consensually because definitions and uses vary, and it is often associated with other techniques (i.e. personification). Despite those incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Another example of CoPF can be found in the musical Singin' in the Rain (Donen and Kelly, 1952). Indeed, in Pager-McClymont (2021, 2022, I argue that the metaphor SADNESS IS RAIN is a prototypical instance of PF. However, the lyrics of the song 'Singin' in the Rain' provide the converse of this mapping: Come on with your rain, I've got a smile on my face!…”
Section: Other Examplesmentioning
confidence: 96%
See 3 more Smart Citations
“…Another example of CoPF can be found in the musical Singin' in the Rain (Donen and Kelly, 1952). Indeed, in Pager-McClymont (2021, 2022, I argue that the metaphor SADNESS IS RAIN is a prototypical instance of PF. However, the lyrics of the song 'Singin' in the Rain' provide the converse of this mapping: Come on with your rain, I've got a smile on my face!…”
Section: Other Examplesmentioning
confidence: 96%
“…In Pager-McClymont (2021), I developed a model of PF using an interdisciplinary approach. The need for an updated and systematic model of PF stemmed from education, as the concept of PF is included in the English National Curriculum (Department for Education, 2013aEducation, , 2013b, and thus likely taught in schools.…”
Section: Pager-mcclymont (2023) Stylistic Model Of Pathetic Fallacymentioning
confidence: 99%
See 2 more Smart Citations
“…The first of these theses is by Kimberley Pager McClymont (University of Huddersfield (UK), supervisors Louise Nuttall and Lesley Jeffries). Pager-McClymont (2021) used cognitive stylistics to explore pathetic fallacy, arguing that little empirical research has been conducted into what pathetic fallacy is linguistically. Using data collected from teachers, pager-McClymont found that pathetic fallacy has several effects: to communicate emotions indirectly in texts, to build characters and atmosphere in texts and as a device for plot foreshadowing.…”
Section: Thesesmentioning
confidence: 99%